Influence of Baricity on the Outcome of Spinal Anesthesia With Bupivacaine for Lumbar Spine Surgery. Issue 6 (November 1995) - Tetzlaff, John E.; O'Hara, Jerome; Bell, Gordon; Grimm, Kenneth; Yoon, Helen J.
Abstract : Background and Objectives: Although the majority of elective lumbar spine surgical procedures are performed under general anesthesia, successful use of spinal and epidural anesthesia has been reported. This study was designed to evaluate the influence of baricity on the performance of spinal anesthesia for lumbar spine surgery. Methods: The study was performed on 53 demographically similar American Society of Anesthesiologists status 1 and 2 patients who were randomly assigned to receive spinal anesthesia with 15 mg of bupivacaine along with 0.2 mg of epinephrine as either 3 mL 0.5% plain bupivacaine (I group) or 2 mL 0.75% bupivacaine (Sensorcaine Spinal, Astra, Westborough, MA) premixed in 8.25% glucose (H group). All blocks were placed with a 22-gauge Quincke needle (Becton Dickinson, Franklin Lakes, NJ) at the L3-L4 interspace with the patient in the sitting position. Subsequent data, collected by a blinded observer, included onset of motor and sensory anesthesia, highest sensory level achieved, maximum changes in heart rate and blood pressure, need for treatment of heart rate or blood pressure decreases, failed blocks, and need for supplemental local anesthetic injection to complete incision or wound closure. Results: The time to onset for complete motor and sensory block was significantly longer in the I group. The maximum sensory level achieved was higher in the H group, and the maximum drop in blood pressure and number of interventions to treat heart rate and blood pressure were greater in the H group. There were two failed blocks, which were repeated successfully, in the H group. The need for local anesthetic infiltration of the wound with incision and closure was greater in the H group. Conclusions: Plain bupivacaine is superior to hyperbaric bupivacaine for spinal anesthesia for elective lumbar spine surgery.